Deliver us from evil - Baldacci, David; McLarty, Ron. (New York : Hachette Audio, 2010)
In this follow-up to The Whole Truth, elusive operative Shaw is once again on the heels of vindictive businessman Evan Waller, this time in the peaceful village of Provence. As Waller looks to build a fortune by wiping out millions of lives, Shaw prepares to take him down. Enter Reggie Campion, an agent for a clandestine English vigilante group. With her own intentions for Waller, she enters a deadly game of cat and mouse with Shaw.
Read by Ron McLarty.
Unabridged.
Compact discs.
Duration: 14:30:00.
Keywords: Women journalists -- Fiction; International relations -- Fiction; Spy stories; Suspense fiction; Audiobooks